The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1155/2014/418705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hyeonggaeyeongyo-Tang in Ovalbumin-Induced Allergic Rhinitis Model

Abstract: Allergic rhinitis (AR) is an allergic inflammation of the nasal airways. The prevalence of AR is increasing worldwide. We investigated whether Hyeonggaeyeongyo-tang (HYT) is effective to suppress the progression of AR induced by ovalbumin (OVA). Male BALB/c mice were used for this study. Allergic rhinitis was induced by OVA. Treatment with HYT was assessed to study the effect of HYT on allergic rhinitis in mice. Histological analysis, immunohistochemistry, multiplex cytokine assay, blood analysis, and cell via… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
0
12
0
1
Order By: Relevance
“…Loerbroks et al ( 32 ) reported that the prevalence of asthma among obese women was almost twice as high as among normal weight women, and a causal relationship between asthma and incident weight gain cannot be excluded. In an animal model study, Hong et al ( 33 ) observed that normal group mice exhibited increased weight compared with AR mice. The current study indicated that food intake was decreased and that weight increase was lower in AR group mice.…”
Section: Discussionmentioning
confidence: 99%
“…Loerbroks et al ( 32 ) reported that the prevalence of asthma among obese women was almost twice as high as among normal weight women, and a causal relationship between asthma and incident weight gain cannot be excluded. In an animal model study, Hong et al ( 33 ) observed that normal group mice exhibited increased weight compared with AR mice. The current study indicated that food intake was decreased and that weight increase was lower in AR group mice.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have successfully established different animal models of AR by using OVA as an allergen and Al(OH) 3 as an adjuvant [35, 36]. In this study, a rat model of AR was successfully established through intraperitoneal injection of OVA and Al(OH) 3 suspension and nasal instillation with 5% OVA solution.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous animal study, HYT had antiallergic effects, inhibiting the increase of the levels of IL-4, IL-13, leukemia inhibitory factor (LIF), eosinophils, neutrophils, monocytes, basophils, lymphocytes, and WBC in ovalbumin-induced AR model [ 10 ]. Based on previous studies, we hypothesized that IgE and eosinophils will be suppressed in patients with AR; however, current study showed no decrease in IgE and eosinophils in AR patients.…”
Section: Discussionmentioning
confidence: 99%
“…Park and Hong reported that HYT has anti-inflammation effects for AR via the suppression of NF- κ B activation and iNOS production in BALB/c mice [ 9 ]. Hong et al reported that HYT reduces infiltration of inflammatory cells and mast cells into the nasal cavity and reduces the levels of cytokines and leukocytes in the blood in an ovalbumin-induced AR model [ 10 ]. In a clinical study, HYT has shown effectiveness in the treatment of adult patients with acne vulgaris [ 11 ].…”
Section: Introductionmentioning
confidence: 99%